Neurological Basis of AMP-Dependent Thermoregulation and its Relevance to Central and Peripheral Hyperthermia. Issue 2 (February 2013) - Muzzi, Mirko; Blasi, Francesco; Masi, Alessio; Coppi, Elisabetta; Traini, Chiara; Felici, Roberta; Pittelli, Maria; Cavone, Leonardo; Pugliese, Anna Maria; Moroni, Flavio; Chiarugi, Alberto
Therapeutic hypothermia is of relevance to treatment of increased body temperature and brain injury, but drugs inducing selective, rapid, and safe cooling in humans are not available. Here, we show that injections of adenosine 5′-monophosphate (AMP), an endogenous nucleotide, promptly triggers hypothermia in mice by directly activating adenosine A1 receptors (A1R) within the preoptic area (POA) of the hypothalamus. Inhibition of constitutive degradation of brain extracellular AMP by targeting ecto 5′-nucleotidase, also suffices to prompt hypothermia in rodents. Accordingly, sensitivity of mice and rats to the hypothermic effect of AMP is inversely related to their hypothalamic 5′-nucleotidase activity. Single-cell electrophysiological recording indicates that AMP reduces spontaneous firing activity of temperature-insensitive neurons of the mouse POA, thereby retuning the hypothalamic thermoregulatory set point towards lower temperatures. Adenosine 5′-monophosphate also suppresses prostaglandin E2-induced fever in mice, having no effects on peripheral hyperthermia triggered by dioxymetamphetamine (ecstasy) overdose. Together, data disclose the role of AMP, 5′-nucleotidase, and A1R in hypothalamic thermoregulation, as well and their therapeutic relevance to treatment of febrile illness.